M.Koshgari's Work” Devonu Lug’oti-T- Turk” and the Issues of Structural-Semantic Analysis - Basoat Kimsanboyeva (Zien Journals, 2023)
The article covers the specifics of quantitative expressive vocabulary units and the issues of their expression in the work ”Devonu lug’oti-t- turk”
Keywords: quantitativity; lexicography; lexicographic work; singular and plural forms